Cultural Categories and Gender Representation in "English Starter" by Bachtiar Bima M. And Friends - Marwati, Wa; Saragih, Gustaman; Rohmah S., Oom (INFERENCE: Journal of English Language Teaching, 2024)
This research examines the cultural categories and gender representation in the English textbook "English Starter" for seventh-grade junior high school students. The study uses Chao's cultural type theory (2011) and Susanto's gender theory (2021). The results show that 61% of the pictures are Universality across Culture, 28% Source Culture, 4% International Culture, 7% intercultural Interaction, and 0% Target Culture. In terms of gender representation, male gender names are represented 49% and female 51%, while female gender is represented 51% and female 52% in address terms, identity markers, adjectives, and nouns. This uneven presentation of cultural categories highlights the need for a more comprehensive approach to curriculum development. The book also demonstrates gender equality, with female gender being more dominant than male, avoiding bias and boosting women's confidence.